KOMPETENSI PEGAWAI BAGIAN OTONOMI DAERAH TERHADAP PENYUSUNAN LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH KABUPATEN KUTAI TIMUR - Fl Sudiran Ibnu Tahiyatul Muhammad Maulidan (ADMINISTRASI PUBLIK, 2017)
This study is intended to determine the competence of employees in Section Autonomous Region Secretariat of the East Kutai Regency in preparing the reports of Regional Government, therefore, the researchers formulated the hypothesis